Regional Economic Outlook, October 2019, Asia Pacific. (Regional Economic Outlook, 2019)
Growth in Asia is expected to moderate to 5.0 percent in 2019 and 5.1 percent in 2020 (0.4 and 0.3 percentage point lower than projected last April, respectively). A marked deceleration in merchandise trade and investment, driven by distortionary trade measures and an uncertain policy environment, is weighing on activity, particularly in the manufacturing sector.